Hourly price elasticity pattern of electricity demand in the German day-ahead market - Andreas Knaut; Simon Paulus (Institute of Energy Economics at the University of Cologne (EWI), 2016)
System security in electricity markets relies crucially on the interaction between demand and supply over time. However, research on electricity markets has been mainly focusing on the supply side arguing that demand is rather inelastic. Assuming perfectly inelastic demand might lead to delusive statements regarding the price formation in electricity markets. In this article we quantify the short-run price elasticity of electricity demand in the German day-ahead market and show that demand is adjusting to price movements in the short-run. We are able to solve the simultaneity problem of demand and supply for the German market by incorporating variable renewable electricity generation for the estimation of electricity prices in our econometric approach. We find a daily pattern for demand elasticity on the German day-ahead market where price-induced demand response occurs in early morning and late afternoon hours. Consequently, price elasticity is lowest at night times and during the day. Our measured price elasticity peaks at a value of approximately -0.006 implying that a one percent increase in price reduces demand by 0.006 percent.
Keywords: C26; L94; Q21; Q41; 330; Electricity markets; Hourly price elasticity of demand; Empirical demand analysis